A new generatrix of the cavity profile of a diaphragm compressor. (July 2014) - Li, Jiyang; Liang, Lin; Jia, Xiaohan; Peng, Xueyuan
The small flowrate and the diaphragm's short life are two shortcomings of the diaphragm compressor. This paper presents a new generatrix of the cavity profile of a diaphragm compressor to increase cavity volume and decrease diaphragm's radial stress. To verify the design theory, the radial stresses on the oil side of the diaphragm in the cavities with the new and traditional generatrices were tested, and the experimental radial stresses agreed with the theoretical values. As the most important evaluation criteria of the cavity profile, the volumes of the cavities with different generatrices and the radial stress distribution of the diaphragm within were investigated under various design conditions. The results showed that the volume of the cavity with the new generatrix was about 6.5% larger than that with the traditional generatrix under the same design condition. Otherwise, with the same cavity volume and radius, the maximal radial stress of the diaphragm in the cavity with the new generatrix decreased by 10.3% stably, compared to that in the cavity with a traditional generatrix. Likewise, in the diaphragm's centric region where the additional stress caused by the discharge holes occurred, the maximal radial stress of the diaphragm in the cavity with the new generatrix decreased about 11.5%.